ANALISIS KADAR GLUKOSA JERUK LOKAL PROVINSI BENGKULU MENGGUNAKAN METODE LUFF SCHOORL - Nita Anggreani; Siti Anisah (Universitas Pahlawan Tuanku Tambusai, 2021)
People in Bengkulu Province generally consume 3 (three) types of oranges, namely Kalamansi Oranges, Gerga Oranges, and Brastagi Oranges. Orange Gerga is a local variety originating from Bengkulu Province, to be precise from Rimbo Pengadang District, Rejang Lebong Regency. While Kalamansi Oranges and Brastagi Oranges are citrus varieties originating from outside the region that has been widely planted by people in Bengkulu. The sweet taste of these three oranges is different which indicates the difference in the sugar content in them. This study aims to analyze the glucose content in the three oranges. The analysis method uses the Luff Schoorl method according to SNI 01-2891-1992. The sampling technique used was purposive sampling. Each sample of orange juice as much as 5 grams was analyzed up to three times. The results showed that the highest glucose levels were in Kalamansi Oranges (0.58%), Brastagi Oranges (0.48%) and the lowest was Gerga Oranges (0.44%).